Money, Trade, and Prices–A Test of Causal Primacy - Copeland, Morris A. (Quarterly Journal of Economics, 1929)
Equation of exchange restated, 649. — Working's theory of the isolation of cyclical variations in money and prices, 649. — Mitchell's theory of the primacy of the pecuniary volume of trade, 650. — Cycles of P and M, 652. — And of T and V, 654. — Working's two basic propositions examined, 656. — Seasonals of T, M, and V, 657. — Seasonals of PT plus R and MV, 659. — Cycles of PT plus R and MV, 661. — Bearing of these comparisons on Mitchell's hypothesis, 663. — Conclusions, 664.